Addressing the ongoing English language growth of international students : resource document. - Rochecouste, Judith; Oliver, Rhonda; Mulligan, Denise; Davies, Martin (Australian Learning and Teaching Council, 2010)
This report presents the outcomes of The English Language Growth (ELG) Project, a large scale project conducted in five Australian universities in 2008-09 to address the ongoing English language development of international students from non-English speaking backgrounds. The study focused on the factors influencing the growth in their English language competence over time and investigated the relationship between academic success and two factors affecting language development: 1) language and academic learning strategy use and 2) affective learning variables (e.g., motivation, anxiety, beliefs). This is the second section of the report, comprising appendices, which include copies of all survey instruments along with extended extracts from the qualitative data provided by students.